Rancang Bangun Mesin Penyerut Es Batu - Faisal Ahmad; Ardin Wiranata; Jabal Nur; Syukur Muzakkir (Program Pendidikan Vokasi Teknik Mesin, 2023)
The use of ice cubes is very important to preserve foodstuffs, especially for fishermen ice cubes play an important role in preserving marine catches such as fish, shrimp, squid and so on. The manufacture of this tool aims to increase effectiveness and efficiency in the process of crushing ice cubes. This tool uses a gasoline motor as the main mover, the pulley diameter on the motor is 7.62 cm and the pully diameter on the blade is 35 cm, the blade shaft diameter is 20 mm. Frame height and length 80 cm, frame width 41 cm. The funnel length is 100 cm, the funnel width and height are 30 cm. The knives on this shredder are 14 pieces with stainless steel. In the testing process, this tool was able to crush ice blocks of 56 kg within 2.8 minutes. There are several advantages of an ice cube crusher that is portable or can be used anywhere, the process of crushing ice cubes uses a fast time. The disadvantages of this tool are that it requires human power to push the material so that the chopped results are maximum and even, during the testing process this tool has shifted, so it requires a prop on the foot to maintain the stability of the tool so as not to shift left, right and forward.